The risk of harm whilst waiting for varicose veins procedure. (February 2023) - Bootun, Roshan; Burrows, Mandy; Chowdhury, Mohammed M; Stather, Philip W; Al-Jundi, Wissam
Introduction: Varicose veins (VV) negatively impact quality of life (QoL) and have risks of major complications including bleeding, ulceration and phlebitis. During the COVID-19 pandemic, the VSGBI (Vascular Society of Great Britain and Ireland) and GIRFT (Get It Right First Time) classified VVs as lowest priority for intervention. Objective: This study aims to determine harm caused and the impact on the QoL on patients waiting for their VVs procedures for more than 1 year. Methods: This was a prospective study conducted at the Norfolk and Norwich University Hospital (NNUH). Patients with VVs awaiting intervention for >1 year were included in the study. Patients with CEAP C6 disease were considered to be too high risk to be invited for treatment during the Covid-19 pandemic. Patients were sent QoL questionnaires and underwent a telephone consultation to assess harm. Both generic (EQ-VAS and EQ-5D) and disease-specific (AVVQ and CIVIQ-14) instruments were utilised. There were no control groups available for comparison. Results: 275 patients were identified (37.1% male) with median time on waiting list of 60 weeks (IQR 56–65). 19 patients (6.9%) came to major harm, including phlebitis (3.6%), bleeding (1.8%) and ulceration (1.8%). Fifty-two patients (18.9%) had minor harm, including worsening pain (12.7%) and swelling (6.2%). 6.9% reported psychological harm. Rising CEAP stage was also associated with worsening level of harm in patients with C5-6 disease ( p < 0.0001). Only 8.7% stated they would decline surgery during the pandemic. 104 QoL questionnaires were returned. Median EQ-VAS and EQ-5D was 75 (IQR: 60–85) and 0.685 (0.566–0.761), respectively. Median AVVQ score was 23.2 (14.9–31.0) and CIVIQ-14 score was 33 (21–44). ConclusionsThis study highlights the impact of delaying VVs surgery during a pandemic. A significant rate of both major and minor as well as psychological harm was reported. In addition, VVs had a significant detriment to quality of life.